Evaluating The Performance of Inventory Management The Production Division of PT. Tiga Serangkai Surakarta as a Case Study - Maryati, Sri (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
This research aims to understand the process of production and to analyze the performance of inventory system on production division of PT. Tiga Serangkai. The data has been gathered from direct observation of the process production and warehouse and the interview with the production employee, the employee of warehouse division, supervisor of purchasing and finance manager. This research demonstrates that inventory system performance of PT. Tiga Serangkai Surakarta can be optimized through the determination of inventory policy, applying a model minimum and maximum inventory that considers the safety stock in accordance with service level plan, implementing model Reorder Point (ROP) which can be used as guidelines in charging supply back, and applying the model economic ordering quantity. In doing so, they can save the cost of inventory. Keywords: inventory management, economic order quantity (EOQ), PT. Tiga Serangkai